Análise do processo de financeirização do setor automotivo - Carmo, Marcelo José do (2017)
The automotive industry undergoes an increasing process of financialization. Financialization has been considered as the preference for capital appreciation through financial activities more than through productive activities. There is, in this process, a tendency for capital to appreciate through activities that do not need to go through production or take place after the production itself. In addition, the sector has become the object of acquisitions and increased participation of banks, investment funds and financial institutions in their property rights. In this way, there is enormous pressure from senior executives and shareholders for an ever-greater return on investment. This maximization of shareholder value has become a recurrent practice for the automakers, where the pursuit of profit reaches 12, 15% of profitability on capital employed, yearly, through financial activities rather than in the mature and cyclical market for automotive products, historically performed poorly and narrow profit margins. It is only through the intensification of financial activities such as leasing, financing and other "products" launched by its subsidiaries that the automakers have achieved the profitability required by shareholders and controllers. In order to make this research feasible, a multi-case study was used to select the five largest automotive companies worldwide, according to data from the International Organization of Automobile Manufacturers, OICA. The top five automakers in 2014 were Toyota, Volkswagen, GM, Hyundai and Ford. In order to analyze financialization, five component categories of this process were investigated, such as: proportion of the profit coming from the finances compared to the profit obtained by the real production; shareholding composition of companies; stock acquisitions; origin of corporate officers; payment of dividends to shareholders, as well as compensation to executives, workers' wages and employment. The central idea of this work is that financialization is one of the main economic characteristic of contemporary capitalism. We hoped, with this work, to contribute to the research agenda of Economic Sociology, current that defends the unification of the various social sciences in the explanation of economic phenomena. In this sense, we were able to know in a broader way the process of financialization of the automotive industry, one of the largest and most important industrial sectors of the economy.